Representations of rural lesbian lives in young adult fiction. Issue 3 (4th May 2017) - Keys, Wendy; Marshall, Elizabeth; Pini, Barbara
ABSTRACT: This paper examines representations of rural lesbian lives in three young adult novels. The novels analysed are Beauty of the broken by Tawni Waters (2014 ), Julie Anne Peters (2005 ) Pretend you love me, and Forgive me if you've heard this one before by Karelia Stetz-Waters (2014 ). The first of the novels by Waters (2014 . Beauty of the broken . New York, NY: Simon Pulse) presents a very negative portrait of rural life for queer youth. Its message is that the only positive queer life is one that is lived in the urban. In contrast, the texts by Peters (2005 . Pretend you love me . New York, NY: Little Brown) and Stetz-Waters (2014 . Forgive me if you've heard this one before . Portland, OR: Ooligan Press) present rural spaces as potentially both inclusive and exclusive for queer youth. These novels also demonstrate that urban spaces can be equally problematic for queer youth. While we do not discount that Waters (2014 . Beauty of the broken . New York, NY: Simon Pulse) description of rural life may be the experience of some queer youth, we argue that the novels by Peters (2005 . Pretend you love me . New York, NY: Little Brown) and Stetz-Waters (2014 . Forgive me if you've heard this one before . Portland, OR: Ooligan Press) offer a more nuanced and complicated notion of place and its relationship to non-normative sexual subjectivities.